A Systematic Review of the Pharmacokinetics of Antiepileptic Drugs in Neonates With Refractory Seizures - Tulloch, Joanie K. (Pediatric Pharmacy Advocacy Group, 2012)
BACKGROUND: Neonatal seizures are associated with neurological sequelae and an increased risk of epilepsy later in life. Phenobarbital and phenytoin remain the antiepileptic drugs (AEDs) most commonly used to treat neonatal seizures, despite their suboptimal effectiveness and safety. As a result, other AEDs, such as levetiracetam and topiramate, are often used in neonates with refractory seizures, despite limited data and off-label use. OBJECTIVES: To systematically review published pharmacokinetic data for second-line AEDs used in neonates with seizures and to provide dosing recommendations for these agents in the neonatal population. METHODS: A literature search was conducted in PubMed (1949-May 2012), Medline (1950-May 2012), and Embase (1980-May 2012). Each study was ranked according to the quality of evidence it provided, based on the classification system developed by the US Preventive Services Task Force. Information extracted from each study included study design, number of subjects, gestational and postnatal age, AED dosage regimen, pharmacokinetic parameters, pharmacokinetic model, AED serum concentrations, and sampling times. RESULTS: Nineteen relevant pharmacokinetic studies involving a total of 8 different drugs were identified. No prospective, randomized, controlled studies (level I evidence) or nonrandomized controlled studies (level II-I evidence) were identified; 2 studies were prospective, nonrandomized, uncontrolled (cohort) studies (level II-2 evidence), 11 studies obtained evidence from multiple time series (level II-3 evidence), and 6 studies were case reports or descriptive studies (level III evidence). CONCLUSIONS: There are limited pharmacokinetic data for the use of carbamazepine, levetiracetam, lidocaine, paraldehyde, topiramate, valproic acid, and vigabatrin for neonates with seizures refractory to treatment with first-line antiepileptic agents. Further research is needed to elucidate target AED serum concentrations (if any) required to optimize effectiveness and minimize dose-related adverse effects in neonates.